HUBUNGAN PEMAKAIAN KONTRASEPSI SUNTIK 3 BULAN DENGAN KENAIKAN BERAT BADAN AKSEPTOR KB DI BPM ENDAH SETIATI, SST DESA TONGAS WETAN: Correlation between 3-Month Injection Contraceptive Use and Weight Gain in Family Planning Acceptors at Endah Setiati, SST Independent Midwife Practice Tongas Wetan Village - Husnah, Shoimatul (Forind Press, 2024)
Injection contraception is a contraceptive method that is widely used in Indonesia. The proportion of injection contraception use was 62.77%. Most acceptors of 3-month injection KB experience an increase in body weight. This is because progesterone stimulates the appetite control center in the hypothalamus, thereby influencing eating behavior. One study showed that many injecting contraceptive users stopped due to side effects such as menstrual disturbances, weight gain, headaches, and stomach discomfort. The purpose of this study was to determine the correlation between the use of 3-month s injection contraception and the increase in the weight of family planning acceptors at Endah Setiati, SST Independent Midwife Practice Tongas Wetan village. This study used a retrospective, using secondary data. With correlation research design with a cross sectional study approach. The population in this study was the number of acceptors of 3-month s injectable family planning at Endah Setiati, SST Independent Midwife Practice. From January to December, 90 people using the total sampling technique and statistical tests used the Chi square test. The results of this study revealed that of the 90 acceptors of the 3-month s injection, most of the acceptors used it for a long time and experienced weight gain, namely 40 people (44.4%). The results of the Chi Square statistical test obtained p-value = 0.126. However, it can be concluded that there is no correlation between the use of 3-month s injectable birth control and weight gain in Endah Setiati, SST Independent Midwife Practice in Tongas Wetan village. The suggestion of this research, will be able to have an impact on midwifery services in the community, especially in providing explanations to patients about the side effects of using 3-month injectable birth control.